Rac-N,N `-Dimethyl-N,N `-(1,1 `-binaphthyl-2,2 `-diyl)diformamide - Zeng, J.; Ng, S.W. (International Union of Crystallography, 2011)
The molecule of the title compound, C(24)H(20)N(2)O(2), lies on a twofold rotation axis that relates one 2-(N-methylformamido) naphthyl unit to the other. The N-methylformamido substituent is twisted by 54.9 (1)degrees with respect to the naphthalene fused-ring system; the two fused-ring systems are themselves twisted by 70.3 (1)degrees.